2001
DOI: 10.1021/ie0005349
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Cadmium from Phosphoric Acid Using Resins Impregnated with Organophosphorus Extractants

Abstract: In the first part of this work, Amberlite XAD-7, impregnated with Cyanex 301, is selected among several supports and organophosphorus extractants for its high affinity for cadmium in phosphoric acid solutions. Initially, the work focuses on the study of cadmium extraction and stripping, in both batch and column systems, using synthetic solutions. This extraction system can be efficiently used for the recovery of cadmium from concentrated phosphoric acid solutions (up to 12 M). Cadmium can be removed from loade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…[44,45] The diffusion coefficient for external mass transfer resistance was 3.7 10 26 m s 21 , while the effective diffusivity was 0.44 10 212 m 2 s 21 . This value of the intraparticle diffusion coefficient is consistent with the diffusivities obtained by Juang and Lin, [44,45] in the case of Amberlite XAD-2 and [17] they obtained intraparticle diffusivities in the range 0.2 Â 10 212 -3.8 Â 10 212 m 2 s 21 (higher than the diffusivities obtained with Amberlite XAD-2 under similar experimental conditions). Serasols et al found that the effective diffusion coefficient (for Au and Zn recovery from HCl solutions using DEHPA/Amberlite XAD-2) varied linearly with the initial concentration: [49,50] the values obtained for a concentration comparable to those we used was of the same order of magnitude (0.2 Â 10 212 -1.4 Â 10 212 m 2 s 21 ).…”
Section: R Navarro Et Al 290supporting
confidence: 91%
See 1 more Smart Citation
“…[44,45] The diffusion coefficient for external mass transfer resistance was 3.7 10 26 m s 21 , while the effective diffusivity was 0.44 10 212 m 2 s 21 . This value of the intraparticle diffusion coefficient is consistent with the diffusivities obtained by Juang and Lin, [44,45] in the case of Amberlite XAD-2 and [17] they obtained intraparticle diffusivities in the range 0.2 Â 10 212 -3.8 Â 10 212 m 2 s 21 (higher than the diffusivities obtained with Amberlite XAD-2 under similar experimental conditions). Serasols et al found that the effective diffusion coefficient (for Au and Zn recovery from HCl solutions using DEHPA/Amberlite XAD-2) varied linearly with the initial concentration: [49,50] the values obtained for a concentration comparable to those we used was of the same order of magnitude (0.2 Â 10 212 -1.4 Â 10 212 m 2 s 21 ).…”
Section: R Navarro Et Al 290supporting
confidence: 91%
“…The dry impregnation of the resin was actually performed by contact of 5 g of conditioned Amberlite XAD-7 with 25 mL of ketone for 24 hours. [17] Varying amounts of Cyanex 921 diluted in ketone (0.5 M) were added, under agitation, to resin slurry for 24 hours. The solvent was then slowly removed by evaporation in a roto-vapor.…”
Section: Resin Impregnationmentioning
confidence: 99%
“…oxides (Syers, 2001). Some elements, such as Cd (Hinojosa Reyes et al, 2001) and REE (Habashi, 1985), can easily be precipitated from solution through a neutralization processes, but this technique cannot be used for the elimination of impurities from phosphoric acid if the acidity of the solution is to be maintained. In addition, the precipitate is very difficult to filter, and a typical product usually contains a large portion of co-precipitated impurities.…”
Section: Recovery Technologiesmentioning
confidence: 99%
“…Solvent extraction has been found to be a very promising process for industrial recovery or removal of many elements (Abdel-Khalek et al, 2011;Amin et al, 2010;Radhika et al, 2010), and it has been proven to be effective in removing U, REE, Cd, and other metals (Table 4). However, solvent extraction has limited industrial application due to its unfavorable economics (high prices of reagents), technical challenges (high loss of solvent, extractant dispersion, introduction of new impurities), and environmental concerns (pollution of solvent and formation of new impurities) (Hinojosa Reyes et al, 2001;Sadegh Safarzadeh et al, 2007).…”
Section: Recovery Technologiesmentioning
confidence: 99%
“…Keywords: valeric acid; extractant-impregnated resin; fixed-bed column; tri-n-butyl phosphate; back-extraction NOTATION a average radius of the resin particle (dm) BV Bed volume calculated by eqn (1) (dm 3 ) C A analytical (total) concentration of valeric acid in the aqueous solution (mol dm −3 ) C A average concentration of valeric acid in the EIR bed at the bed saturation point, estimated either by eqn (2) or eqn (5) (mol dm −3 of fresh resin) C total concentration of valeric acid in the aqueous solution accumulated in the column at the bed saturation point, estimated by eqn (4) The extractant impregnated resin (EIR) may be used to carry out the solute extraction in a stirred tank but, as with adsorption, using the process in a fixed or fluidized bed would be the most common industrial process. The operation of these processes is straightforward, although their analysis is more complex.…”
Section:  2005 Society Of Chemical Industrymentioning
confidence: 99%